Escola pública: "gestão democrática", colegialidade e individualismo - António A. Mendes Neto (Universidade do Minho, 2004)
This paper presents a set of reflections on the potentialities that the portuguese public school (especially the secondary public school which is the subject here) has fulfilled in the frame of the "democratic management", as a broad space for collegial exercise of the teaching profession and of the democratic socialization of students, although we highlight specifically the dimension of the secondary school as a context for the teachers´ work. This feature cannot, however, be disconnected from a critical perspective that contemplates the limits of such an organization of the (democratic) management of schools, in resemblance, as a matter of fact, of what is happening in the broader field of the management of societies. The emphasis goes to the fact that, in spite of all the collegial organization built mainly around the teaching body of a school, there is a deficit of democraticity in the school which frails the political project of an active citizenship. We conclude by defending the idea that the solution for this problem is the democratic deepening of the school organization.